Norwegian supply chain collaboration when it is urgent to reduce food waste: the relation between efforts for good outcomes and engaging in RRI process dimensions - Ellen-Marie Forsberg; Ina Charlotte Berntsen; Andreas Brekke; Anne-Grete Haugen; Aina Elstad Stensgård; Nhat Strøm-Andersen; Erik Vold; Julia Szulecka (Journal of Responsible Innovation)
Food waste is a major source of avoidable greenhouse gas emissions. Responsible research and innovation (RRI) should contribute to meeting urgent challenges like climate change. This paper discusses collaborative innovations to reduce food waste and analyses this from the perspective of RRI, understood as purpose and process requirements. We study to what extent the focus on a responsible innovation outcome in Norwegian food supply chain collaboration corresponds with respecting the process dimensions of RRI, based on interviews and a consensus conference process. This contributes to understanding whether an urgent purpose can facilitate or is a barrier to the process dimensions of RRI. We find that besides aiming for a good outcome, the food companies intend to innovate in an inclusive and reflective way. The sustainability agenda as an important purpose for innovation, and the urgency of the goal of reducing food waste, is in our study well aligned with RRI.